Synthesis of Optimal Isolation Systems of Hand-Transmitted Vibration - Marek Książek (Shock and Vibration)
In this article a procedure is presented for the analytical synthesis of optimal vibration isolation for a hand-arm system subjected to stochastic excitation. A general approach is discussed for a selected vibration isolation criterion. The general procedure is illustrated by analytical examples for different hand-arm systems described by their driving-point impedances. The influence of particular forms of excitation and the structure of the vibroisolated hand-arm systems on the resultant vibration isolation is then discussed. Some numerical examples illustrating the procedure have also been included.